Massed prolonged exposure therapy for PTSD and depression - Qodashe, Mandisa (Rhodes University, 2026)
Approximately 97.6% of South African university students report exposure to a potentially traumatic event (PTE) (Padmanabhanunni, 2020). University students are thus at an increased risk of developing post-traumatic stress disorder (PTSD). Furthermore, of those with PTSD, 30-50% will experience severe major depressive disorder (Campbell et al., 2007). However, there remains a large treatment gap that is characteristic of university counselling centres. Consequently, this study employed a mixed methods design to investigate the effectiveness, acceptability and feasibility of Massed-Prolonged Exposure (MPE) in reducing PTSD as the primary outcome and comorbid depression as the secondary outcome in a South African university. A Single-Case Experimental Design (SCED) was employed to assess MPE’s effectiveness, whilst interviews were conducted after the intervention to assess the participants perceptions related to the feasibility and acceptability of MPE. Participants (n = 2) were recruited from Rhodes University through purposive sampling. Initial screening utilized the PTSD Diagnostic Scale for DSM-5 (PDS-5) and Patient Health Questionnaire-9 (PHQ-9) to confirm PTSD and major depressive disorder (MDD) diagnoses. The PHQ-9 and PTSD Symptom Checklist for DSM-5 (PCL-5) were used for ongoing assessment during the intervention. The participants no longer met the criteria for both diagnoses at the end of the intervention. Reflexive thematic analysis was used to assess the interviews. The findings from these interviews revealed that although participants found the techniques of the intervention initially challenging, they found the treatment helpful. The study provides preliminary evidence supporting the use of MPE in ameliorating PTSD and MDD symptoms. The study also contributes to the literature regarding evidence-based interventions within South African university settings.
a mixed-methods study
Keywords: Post-traumatic stress disorder (http://id.loc.gov/authorities/subjects/sh85105424); Depression, Mental (http://id.loc.gov/authorities/subjects/sh85037053); College students--Mental health (http://id.loc.gov/authorities/subjects/sh2009120677); Clinical Psychology; Prolonged exposure therapy (https://www.wikidata.org/wiki/Q2412412)